PENETAPAN PRIORITAS PENANGANAN PANTAI BERDASARKAN PEMILIHAN JENIS BANGUNAN PADA PROYEK-PROYEK KONSTRUKSI BALAI WILAYAH SUNGAI SULAWESI-I (BWSS-I) - Ratulangi, Deddy R. G.; Manoppo, Fabian J.; Willar, Debby (Sam Ratulangi University, 2017)
The eastern outskirts of North Sulawesi province areas are areas of local government development. Its geographical position which almost entirely consist of coastal areas are ultimately requires protection in the framework of synergy for the holistic government policy. An alternative way to protect the beach is by construct a beach shoreline structures. Coastal protection building type if structurally reviewed consists of 4 (four) main type of building that is Seawall, Groin, Jetty, and Breakwater. These types of coastal protection buildings can be combined. The beaches in the eastern region of North Sulawesi province for this research are Rumbia beach, Walensorit beach, Bukit Tinggi beach, Parentek beach, Atep Oki beach, and Kament beach. The aims of this research are to examine the extent of damage, vulnerability and coastal virtues on the beaches of the eastern ring road of North Sulawesi province and to conduct the process of selecting the type of security building on the eastern coastal beaches of North Sulawesi province if viewed in a priority scale of interest and also to determine the most dominant type of coastal security building to be built on the eastern coastal coasts of North Sulawesi province. In this study, data were analized by using Analytical Hierarchy Process, AHP. Based on the research results obtained, for the type of coastal protection building that is generated are as follows: Rumbia beach: Seawall (24.142%), Breakwater (20.510%), and Seawall + Breakwater (17.965%); Walensorite beaches: Groin (17,671%), Jetty (17,033), and Seawall + Groin (14,528); Bukit Tinggi beaches: Seawall (15.349%), Jetty (12.674%), and Groin (12.609%); Parentek beaches: Seawall (13.149%), Groin (13.132%), and Seawall + Jetty (10,437%); Atep Oki beach: Groin (19.234%), Jetty (15.430%), Seawall + Groin (14.44%); And Kamenti beaches: Seawall (12.763%), Seawall + Breakwater (11.283%), and Breakwater (10.960%). For the type and condition of the eastern coastal shore, the most dominant type of coastal safety building is the Seawall and Groin beach type safety structures. Both types of buildings are very appropriate for large erosion, abrasion and wave rates. While the difference between these two types of coastal safety buildings is the level of sedimentation, which for Seawall is suitable for low sedimentation levels, while Groin is suitable for large sedimentation levels. Keywords: Coastal Protection Structure, AHP, Seawall, Groin, Jetty, Breakwater